Delivering Social Housing: Examining the Nexus between Social Housing and Democratic Planning. Issue 3 (2nd July 2016) - Legacy, Crystal; Davison, Gethin; Liu, Edgar
Abstract: The construction of social housing in gentrifying neighbourhoods can ignite contestation, revealing tensions between economic imperatives, social policy and neighbourhood change. With a view to understanding how the convergence of these agendas preserve unpopular, but socially critical housing infrastructure, the aim of this paper is to explore how the challenges social housing implementation encounters across these agendas intersect with a broader agenda for local democratic planning. Using social housing as our empirical focus and directing attention to the gentrifying local government area of Port Phillip in Victoria, Australia, this paper reveals how a council's main asset to support implementation – its policy frameworks – creates an urban narrative of social inclusivity and diversity. Through this case, we illustrate how elected officials and some residents draw from these policies to interject into episodes of community contestation, which we argue presents opportunities to expose and renew commitments to social housing over space and time.